2019
DOI: 10.21873/cgp.20169
|View full text |Cite
|
Sign up to set email alerts
|

BRD4-Regulated Molecular Targets in Mantle Cell Lymphoma: Insights into Targeted Therapeutic Approach

Abstract: Background: Since bromodomain-containing protein 4 (BRD4) facilitates the transcription of genes important for neoplastic cells in a cancer-type specific manner, BRD4-regulated molecules may also include therapeutic targets for mantle cell lymphoma (MCL), a treatment-refractory subtype of malignant lymphoma. Materials and Methods: In order to uncover direct BRD4regulated targets in MCL, we performed integrated analysis using the pathway database and the results of both geneexpression profiling and chromatin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…BRD4 directly regulates a series of genes related to the B cell receptor signaling pathway. I-BET151 promotes the G1/S cell cycle arrest and apoptosis in BRD4-induced MCL cells, which represents a new strategy for treating MCL disease ( 44 ).…”
Section: I-bet151 Is Effective Against Various Cancersmentioning
confidence: 99%
“…BRD4 directly regulates a series of genes related to the B cell receptor signaling pathway. I-BET151 promotes the G1/S cell cycle arrest and apoptosis in BRD4-induced MCL cells, which represents a new strategy for treating MCL disease ( 44 ).…”
Section: I-bet151 Is Effective Against Various Cancersmentioning
confidence: 99%
“…STAT5 regulates the super-enhancer of the myc gene by means of competition for binding to target sites or regulating histone acetylation in an opposing way to Ikaros ( Katerndahl et al, 2017 ). It was revealed that the genes related to the BCR signal pathway and the IKZF family are presumed to be upstream of the MYC/IRF4 axis ( Tsukamoto et al, 2020 ). In patients with trisomy 12 CLL, IRF4 by means of inducing Ikaros mediates the overexpression of CD49d, which was considered to identify those patients treated with ibrutinib with the characteristics of inferior nodal responses and shorter clinical outcomes ( Fiorcari et al, 2019 ).…”
Section: Ikaros Family Signalingmentioning
confidence: 99%
“…BRD4 inhibitors were suggested to enhance the anti-MCL effect of Len or ibrutinib synergistically. It works even in BTZ-resistant MCL cells ( Tsukamoto et al, 2020 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Total RNA extraction and quantitative RT-PCR (qRT-PCR) were performed, as described elsewhere [27,32,52,53]. Primer sequences for qRT-PCR were as follows: BUB1 FW: 5 -ACC ATT CCA CAA GCT TCC AGT G-3 , BUB1 RV: 5 -TGA AGG CAC CAC CAT GTT TTC C-3 , β-Actin (ACTB) FW: 5 -TTC TAC AAT GAG CTG CGT GTG G-3 , and ACTB RV: 5 -TGG GGT GTT GAA GGT CTC AAA C-3 .…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…Western blotting was performed, as described previously [27,32,52,53], using rabbit anti-BUB1 (Abcam Cat#ab9000, Cambridge, UK) and mouse anti-ACTB (Sigma-Aldrich Cat# A2228, St. Louis, MO, USA) primary antibodies.…”
Section: Western Blottingmentioning
confidence: 99%